Save Ningaloo website - Save Ningaloo (Campaign) ([Perth, W.A.] : Save Ningaloo, 2002)
This website shows the efforts of the Save Ningaloo campaign to protect the Ningaloo Reef, a wild and unique coral reef on the isolated West Australian coastline near Exmouth, said to be under threat from the proposed Coral Bay Resort development at Maud's Landing.
Title from home page (viewed on 14 Feb. 2003)
Text, graphics, video and sound.
Mode of access: World Wide Web. Available at: http://www.saveningalooreef.org
System requirements: Adobe Acrobate Reader; plug-in to view video clips.
Selected for archiving
Keywords: Save Ningaloo (Campaign); Environmental protection -- Western Australia -- Ningaloo Reef; Political activists -- Western Australia -- Ningaloo Reef; Ningaloo Reef (W.A.)